Utilising fraction pieces to improve Year 5 pupil's ability in conceptual understanding and finding equivalent fraction with denominator up to 10 proper fraction / Ensoh Uba - Uba, Ensoh (2015)
There are time when the strategies used in teaching and learning process rendered ineffective to certain pupils. At such, Lucy, Connielia and Wilson my pupils in Year 5, was not able to cope up with the lessons, I gave even after various strategies. This situation motivates me to conduct an action research in my effort to help them. To achieve this, I used an innovation of fraction charts called Fraction Pieces which utilises the use of touchable and movable pieces. Specifically in this action research, I aimed to improve of them ability in expressing understanding conceptual and finding an equivalent fraction with denominator up to 10 of a proper fraction. In order to measure the improvement, I make use of pre-test and post-tests, interviews and observation to collect data. The result shows that they have 100% of increase in conceptual understanding an equivalent fraction with denominator up to 10 of a proper fraction. They also had shown an increase of 100% except Wilson was only 60% increase finding and writing an equivalent fraction with denominator up to 10 of a proper fraction. The result of increase in them score shows the effectiveness of Fraction Pieces. Therefore, I believe that this strategy can also be applied to other school which pupils are having problem with equivalent fraction.